Whitman East & West : new contexts for reading Walt Whitman - Folsom, Ed, 1947- (Iowa Whitman series., 2002)
In Whitman East and West, fifteen prominent scholars track the surprising ways in which Whitman's poetry and prose continue to be meaningful at the beginning of the twenty-first century. Covering a broad range of issues--from ecology to children's literature, gay identity to China's May 4th Movement, nineteenth-century New York politics to the emerging field of normality studies, Mao Zedong to American film--each original essay opens a previously unexplored field of study, and each yields new insights by demonstrating how emerging methodologies and approaches intersect with and illuminate Whit.